Sovietinės televizijos diskurso daugialypumas: oficialumo ir nuoširdumo drama - Pečiulis, Žygintas (Information & Media, 2013)
Straipsnyje analizuojama sovietinio laikotarpio Lietuvos televizija. Pateikiamas Vakarų ir Rytų Europos audiovizualinės masinės komunikacijos istorinės raidos kontekstas, visuomeninių ir valstybinių transliuotojų funkcijų lyginamoji analizė. Pasitelkus sovietmečio dokumentus, televizijos laidų tekstus, televizijos darbuotojų prisiminimus, atskleidžiama audiovizualinės masinės komunikacijos priemonių vieta sovietinėje sistemoje, pateikiamos svarbiausios ideologinės klišės, analizuojamas cenzūros ir asmeninės cenzūros veikimas, televizijos darbuotojų santykio su sistema problema. Reikšminiai žodžiai: audiovizualinė masinė komunikacija, televizija, sovietinės Lietuvos televizija, ideologinės klišės, cenzūra, pranešimo stilistika. Multiplicity of Soviet television discourse: formality and sincerity drama Žygintas Pečiulis Summary Information dosage during the Soviet period was based on noble purposes. Closed borders and information control were the ways to keep the system and persuade society. Peculiarities of society, such as the official doctrine and its treatment on the personal daily level or adaptation and rebellion dilemma determined the formation of multiple television discourses. The documents, memories, scripts of the time allow to reveal the television discourse multiplicity in soviet Lithuania and the intentions of the originators of such discourses. Modern media fall into stagnation, in a strictly regulated environment. However, the pomp of communism coincides with the dynamism and innovation of television. Television was used to promote the principal ideological postulates: internationalism, socialism, the cult of the proletariat and communism, the failure of capitalism, depreciation of independent Lithuania, atheism. The language was pompous, characterized by a combination of belletristic and bureaucratic styles, attention to the correctness. There were plenty of phrases reminiscent of fairy tale and myth phraseology. Key words: audio-visual mass communication, television, the soviet Lithuanian television, ideological clichés, censorship, communication style.